NEW YORK STATE PUBLIC HEALTH COUNCIL PUBLIC HEARING - NOVEMBER 3, 1986 (Tufts Archival Research Center, 2007)
Outline of New York State Public Health Council Public Hearing. Lists comments made by each speaker. Includes arguments against smoking restrictions as well as arguments for non-smokers rights, input from labor unions, legislators, the tobacco industry, and hotel and restaurant advocates, and representatives of minorities.